Regulation of murine natural killer cell commitment - Huntington, Nicholas D.; Nutt, Stephen L.; Carotta, Sebastian (Frontiers in Immunology, 2013)
NK cells can derive from the same precursors as B and T cells, however to achieve lineage specificity, several transcription factors need to be activated or annulled. While a few important transcription factors have identified for NK genesis the mechanisms of how this is achieved is far from resolved. Adding to the complexity of this, NK cells are found and potentially develop in diverse locations in vivo and it remains to be addressed if a common NK cell precursor seeds diverse niches and how transcription factors may differentially regulate NK cell commitment in distinct microenvironments. Here we will summarise some recent findings in NK cell commitment and discuss how a NK cell transcriptional network might be organised, while addressing some misconceptions and anomalies along the way.